PENGISIAN AKI DENGAN BUCK CONVERTER - Yul Antonisfia; era madona (Teknik Elektro Politeknik Negeri Padang, 2013)
Buck converter is one of DC chopper which has the function of stabilizing the voltage to lower voltage where the output voltage is lower than the input voltage without having to remove power is relatively large. By using a buck converter is a high voltage can be reduced to lower as you wish without losing power is relatively large. The voltage output of the buck converter is able to charge the battery. The magnitude of the output voltage depends dutycyle switching generated by the microcontroller. This tool is also equipped with a flow sensor is used to detect the charging current into the battery. If the charging current is reduced, the buzzer will sound. The tool is based microcontrollers using BASCOM ATMEGA8535, which can generate a PWM with dutycyle specified. Dutycyle determined the size of the input voltage and the desired output.